Perbedaan Penurunan Suhu Tubuh Tikus Wistar Jantan Dan Betina Yang Mati Akibat Diinduksi Metanol - Abdul Hakim Nitiprodjo; Titik Kusumawinakhyu (Universitas Muhammadiyah Purwokerto, 2021)
Someone who dies will experience a decrease in body temperature from body temperature at the beginning of death, both within normal and abnormal limits to room temperature. Decrease in body temperature according to sex may differ in duration. Coupled with exposure to methanol, it is also possible to influence a decrease in body temperature of the corpse. This study aimed to analyze the differences in body temperature reduction in male and female Wistar rats induced with methanol.This research is an experimental study with a pre and post test control group design approach. The design of this study was to observe the body temperature of male and female Wistar rats while still alive and after death and the duration of decrease in body temperature of male and female Wistar mice after being induced with methanol. The population studied was male and female Wistar rat. Based on the results from analysis test, it can be concluded that there is no significant difference between the decrease in body temperature of male and female Wistar rats that died induced by methanol, but there is a significant difference between the decrease in body temperature of male and female Wistar rats who died induced by methanol and without methanol.